Twenty-first century and its discontents : how changing discourse norms are changing culture - Simmons, Jack (ed.) (Lanham : Lexington, 2020)
"Philosophers and political theorists tackle the question of cultural transformation in the twenty-first century and the role discourse norms play in producing cancel culture, a counter-sexual revolution, racism and a toxic politics that has left the nation feeling vulnerable and angry"--
Includes bibliographical references and index.
Keywords: Social change; Sex role; Racism -- Political aspects; Political culture